Pattern of Surgical Antibiotic Prophylaxis in A Corporate Hospital of Chattogram - Hossain, Md Akram; Khan, Ayesha Ahmed; Chowdhury, Nasreen; Dey, Pompy; Zahur, Tamanna; Islam, Sumaiya; Das, Raju; Walid, Adnan; Mitun, Sourav Nath; Emu, Showrov Sen; Chowdhury, Faisal; Raju, Md Saiful Islam (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Surgical Site Infections (SSIs) are among the most common postoperative complications, significantly contributing to patient morbidity, prolonged hospital stays and increased healthcare costs. SSIs occur at or near the surgical incision within 30 days of the procedure or one year if an implant is placed. Risk factors include patient-related elements (e.g. Diabetes, obesity), procedural factors (e.g. Duration of surgery, sterilization practices) and perioperative care.Surgical antibiotic prophylaxis, a fundamental part of standard operative procedures to avert infections at the site of surgery, has improved postoperative recovery. Irrational and excessive use of antibiotics is common in surgical prophylaxis, resulting in increased treatment expenditures and antimicrobial resistance. This study aimed to determine the prescription pattern of prophylactic antibiotics in surgeries by different departments of a Corporate Hospital in Chattogram. Materials and methods: A retrospective analytical study included the data of 997 patients, underwent different surgeries at a corporate hospital in Chattogram, Bangladesh, from May 2023 to June 2024. Demographic data, types of surgery, and types of antibiotics used were collected from the hospital's electronic health records and analyzed by using Microsoft Excel 2016. Results: In this study, females were predominant (74.22%) overmales. The mean age was32.37±14.78 years. One-third of our patients belonged to the age group of 21-30 years. The highest bulk of patients (40.56%) were from obstetrics surgery. Ceftriaxone was the most commonly used antibiotic during the 30-60 minutes before incision. The orthopaedic surgery department used Cefazolin in both pre- and post-operative cases. Conclusion: The most used antibiotic for surgical case prophylaxis was Ceftriaxone. To control antimicrobial resistance, it is necessary for every hospital to follow antimicrobial guidelines and antibiotic stewardship program. JCMCTA 2025 ; 36 (1) : 32-37